Hypercapnia is essential to reduce the cerebral oxidative metabolism during extreme apnea in humans - Bain, Anthony R (J Cereb Blood Flow Metab, 2017)
The cerebral metabolic rate of oxygen (CMRO(2)) is reduced during apnea that yields profound hypoxia and hypercapnia. In this study, to dissociate the impact of hypoxia and hypercapnia on the reduction in CMRO(2), 11 breath-hold competitors completed three apneas under: (a) normal conditions (NM), yielding severe hypercapnia and hypoxemia, (b) with prior hyperventilation (HV), yielding severe hypoxemia only, and (c) with prior 100% oxygen breathing (HX), yielding the greatest level of hypercapnia, but in the absence of hypoxemia. The CMRO(2) was calculated from the product of cerebral blood flow (ultrasound) and the radial artery-jugular venous oxygen content difference (cannulation). Secondary measures included net-cerebral glucose/lactate exchange and nonoxidative metabolism. Reductions in CMRO(2) were largest in the HX condition (−44 ± 15%, p < 0.05), with the most severe hypercapnia (PaCO(2) = 58 ± 5 mmHg) but maintained oxygen saturation. The CMRO(2) was reduced by 24 ± 27% in NM (p = 0.05), but unchanged in the HV apnea where hypercapnia was absent. A net-cerebral lactate release was observed at the end of apnea in the HV and NM condition, but not in the HX apnea (main effect p < 0.05). These novel data support hypercapnia/pH as a key mechanism mediating reductions in CMRO(2) during apnea, and show that severe hypoxemia stimulates lactate release from the brain.